FRI0454 Arterial stiffness of the forearm is associated with nail-fold capillary count in ssc: a novel marker of early vasculopathy?. (12th June 2018) - Habing, M.M.; Eman Abdulle, A.; van Roon, A.M.; van Roon, A.M.; van Goor, H.; Bootsma, H.; Smit, A.J.; Mulder, D.J.
Abstract : Background: Microvascular disease, characterised by rarefaction of capillaries, is the hallmark of systemic sclerosis. Remarkably, obliteration of the ulnar and radial artery is regularly observed, implicating involvement of the larger forearm arteries. Pulse wave velocity (PWV) is a widely accepted non-invasive measure for arterial stiffness and may serve as an early biomarker of forearm artery involvement, before the occurrence of irreversible arterial obliteration. Objectives: The aim of the current study was to investigate arterial stiffness of the aorta and of the upper extremities in SSc patients compared to healthy controls and to correlate these findings with nail-fold capillary count, skin involvement, and extent of disease. Methods: In total, 19 SSc patients (median age 51 years, 68% female) and 19 age and gender matched healthy controls (median age 53 years, 68% female) were included. Patients characteristics were obtained and blood was drawn. Measurements of arterial stiffness were carried out by using the SphygmoCor System (AtCor Medical, Sydney, Australia) and pressure waveforms were measured at four sites, i.e. carotid, femoral, brachial, and radial. Aortic PWV was defined as carotid-femoral (cf) PWV. Upper extremity PWV was measured as carotid-brachial (cb) and carotid-radial (cr) PWV, and the ratio between cbPWV/crPWV was used as an indication of the relative change in PWV in the forearm. Capillary count was defined as the mean capillary count per 3 mm of 8 fingers. Skin involvement was assessed by the modified rodnan skin score. The number of ACR/EULAR 2013 criteria points was used as a surrogate for extent of disease. Results: Upper extremity PWV measures were significantly higher compared to aortic PWV in patients and in controls (SSc: p<0.001; HC: p=0.03), but did not significantly differ between both groups (table 1). CbPWV/crPWV ratio correlated strongly with capillary count (r=−0.55, p=0.022, figure 1) in SSc patients with a borderline significant trend in regards to its relation with the extent of disease (r=0.48, p=0.053) and skin involvement (r=0.41, p=0.10). Conclusions: Our findings demonstrate that arterial stiffness of the forearm has a relationship with nailfold capillary count and tends to be associated with the extent of disease in patients with SSc. These preliminary data may suggest that vascular damage may concomitantly occur in both capillaries as well as larger arteries of the forearm, which may potentially serve as a novel tool for assessing of early vascular involvement in SSc. Disclosure of Interest: None declared